Human’s Cultural Consciousness Recovery and Cultural Searching (Housing, Town and City) within Kwan Phayao’s Lake Coast - Chuayounan, Satit (International Journal of Psychosocial Rehabilitation, 2020)
The purposes of this research aimed to study 1) to explore and collect the communities’ cultural data within the Khwan PHAYAO lake coast for creation the cultural mapping 2) to develop the cultural master plan within the Khwan PHAYAO lake coast and 3) to extend the cultural capital and local wisdom for economy and social development within Khan PHAYAO lake coast. The result of the purposes found that: 1) group process of cultural data collection within the Khwan PHAYAO lake coast by knowledge sharing and area-based working together was used for exploration and data collection to create the cultural mapping 2) the cultural master plan for communities development there were three strategies that were economy system development, quality of life development and natural resource and environment management and 3) extending the cultural capital and local wisdom found that (1) the social development; communities got the chance to participate for cultural space development and the members in communities were so proud of their self, and they got more perceptive about local wisdom and (2) the economy development found that the budget of the project was 1,500,000 baht that making the project benefits were 1,668,238 baht.